Cashless economies : costs and benefits - Osland, Asbjørn; Clinch, Nanette (London : SAGE Publications: SAGE Business Cases Originals, 2021)
Many countries are moving in the direction of cashless transactions. The advantages include reduced risk of robbery, quicker processing of transactions, enhanced transparency, and reduced threat of corruption. In addition, the government saves the substantial cost of minting currency. Two concerns remain unresolved: (1) many people still need cash because they have not adapted to the digital age for a variety of reasons, and (2) the threat of identity theft and fraud continues.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic funds transfers